Lactobacillus sakei WIKIM30 Ameliorates Atopic Dermatitis-Like Skin Lesions by Inducing Regulatory T Cells and Altering Gut Microbiota Structure in Mice - Kwon, Min-Sung; Lim, Seul Ki; Jang, Ja-Young; Lee, Jieun; Park, Hyo Kyeong; Kim, Namhee; Yun, Misun; Shin, Mi-Young; Jo, Hee Eun; Oh, Young Joon; Roh, Seong Woon; Choi, Hak-Jong (Frontiers in Immunology, 2018)
Lactobacillus sakei WIKIM30 is a Gram-positive facultative anaerobic bacterium isolated from kimchi, a Korean fermented vegetable food. In this study, we found that WIKIM30 promoted regulatory T cell (Treg) differentiation by inducing dendritic cells with tolerogenic properties. The production of the T helper (Th) 2-associated cytokine interleukin (IL)-4 was decreased, but that of the Treg-associated cytokine IL-10 was increased in splenocytes from ovalbumin-sensitized mice treated with WIKIM30. We also investigated the inhibitory capacity of WIKIM30 on the development of 2,4-dinitrochlorobenzene-induced atopic dermatitis (AD), a Th2-dominant allergic disease in mice. Oral administration of L. sakei WIKIM30 significantly reduced AD-like skin lesions and serum immunoglobulin E and IL-4 levels while decreasing the number of CD4+ T cells and B cells and the levels of Th2 cytokines (IL-4, IL-5, and IL-13) in peripheral lymph nodes and enhancing Treg differentiation and IL-10 secretion in mesenteric lymph nodes. Additionally, WIKIM30 modulated gut microbiome profiles that were altered in AD mice, which showed increases in Arthromitus and Ralstonia and a decrease in Ruminococcus abundance. These changes were reversed by WIKIM30 treatment. Notably, the increase in Ruminococcus was highly correlated with Treg-related responses and may contribute to the alleviation of AD responses. Together, these results suggest that oral administration of L. sakei WIKIM30 modulates allergic Th2 responses and has therapeutic potential for the treatment of AD.